Stratification Categories in Mass Media in 1995–2003 - ГоловляницинаЕкатерина Борисовна (Journal of Economic Sociology, 2010)
Here is the short version of the master thesis that was devoted to the problem of articulation of the stratification categories in mass media press in 1995-2003. The paper analyses the usage of the different categories in scientific sociological papers and mass media press. With the help of the electronic data set “Integrum” the author presents the analysis of the frequencies of these categories usage and meanings that are put into them. The research comprises both stratification and ideological aspects. As the result plenty of cases were described when and how the terms were used in different types of information sources.